Habitat and Density of Crab (Parathelpusha pardus) in the Tanduk River, Rumbio Village, Kampar District, Riau - Azhar, Muhdi; Fajri, Nur El; Fauzi, Muhammad (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
Freshwater crabs have a life cycle entirely in freshwater and play an essential role in the food chain as both omnivores and detritivores. Some freshwater crabs can only be found in clean water, so they can also be used as bioindicators of water quality. This study aims to determine the habitat and density of crabs in the Tanduk River in Rumbio Village and to investigate the relationship between environmental parameters and the density of P. pardus crabs in this area, Kampar District. The study was conducted from March to April 2024 in Rumbio Village, Kampar District, Kampar Regency, Riau Province. The methods used were surveys and literature reviews. The survey method involved direct field visits to the study site. Sampling was conducted three times over a three-week period. The literature review involved collecting secondary data from previous studies and data obtained from local government offices. Primary data consisted of field data, including crab samples that were collected and identified, as well as water quality data. The study found that the density of P. pardus crabs in the Tanduk River in Rumbio Village was 10 individuals at Station 1, 16 individuals at Station 2, and 29 individuals at Station 3. Various factors, including environmental conditions like vegetation and food availability, influenced this. The habitat characteristics supporting the survival of P. pardus crabs based on water quality measurements in Rumbio Village during the study were temperature 27–28°C, turbidity 12–50 cm, pH 7.5–8.5, dissolved oxygen 5.7–7.2 mg/L, free CO₂ 5–17 mg/L, and phosphate 0.0730–0.1327 mg/L.